Molecular Epidemiology of Uranium Exposure: Omics Approaches in Cancer Research - Menahil Rahman (Journal of World Science, 2025)
Uranium poses occupational and environmental risks due to its toxicity and radioactivity. A proven correlation exists between uranium exposure, including radon progeny, and lung cancer in miners. Molecular epidemiology using high-throughput omics has advanced our understanding of these effects, revealing high somatic mutations in p53 and oncogenes, dysfunctions in the DNA repair pathway, and changes in DNA methylation, including global hypomethylation and hypermethylation of genes such as RASSF1A and CDKN2A. MicroRNAs like miR-21, miR-34A, and miR-155 are involved. Metabolomics shows altered lipid metabolism, amino acid turnover, and oxidative stress markers. Integrated omics analyses link molecular changes to apoptosis, mitochondrial dysfunction, and alterations in energy metabolism. Biomarkers such as micronuclei and chromosomal aberrations are associated with exposure and cancer risk. Human studies face challenges like small sample sizes and varied exposure assessment, but multi-omics molecular epidemiology offers significant potential for improved risk assessment and prevention.